The Profesional Competence Improvement of Mathemtics Teachers in Kota Langsa through Maple as Solution for Mathematics problem - fazrina - saumi (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2018)
This community service has purpose to give knowledge for teachers of senior high school (SMA) about using software Maple. Target in this program is teachers, especially mathematics teacher of SMA in Langsa whose has lack of ability in solving excact and numerically problems of mathematics. The direct approach, speech, and practical activities are used as methods in this programm. Speech is performed through socialization in giving information for teachers about benefits of Maple as one of powerful mathematics software in solving mathematics problem. In another side, practice method is performed through training of software Maple for mathematics MGMP`s teachers in Kota Langsa. The result of this programm is ability of teachers using sofware Maple in solving mathematics problems.